Rapid and sensitive detection of genome contamination at scale with FCS-GX - Astashyn, Alexander; Tvedte, Eric S.; Sweeney, Deacon; Sapojnikov, Victor; Bouk, Nathan; Joukov, Victor; Mozes, Eyal; Strope, Pooja K.; Sylla, Pape M.; Wagner, Lukas; Bidwell, Shelby L.; Brown, Larissa C.; et al. (Genome Biology, 2024)
Assembled genome sequences are being generated at an exponential rate. Here we present FCS-GX, part of NCBI’s Foreign Contamination Screen (FCS) tool suite, optimized to identify and remove contaminant sequences in new genomes. FCS-GX screens most genomes in 0.1–10 min. Testing FCS-GX on artificially fragmented genomes demonstrates high sensitivity and specificity for diverse contaminant species. We used FCS-GX to screen 1.6 million GenBank assemblies and identified 36.8 Gbp of contamination, comprising 0.16% of total bases, with half from 161 assemblies. We updated assemblies in NCBI RefSeq to reduce detected contamination to 0.01% of bases. FCS-GX is available at https://github.com/ncbi/fcs/ or https://doi.org/10.5281/zenodo.10651084 .